An Investigation of Securities and Exchange Commission Regulation of Auditor Change Disclosures: The Case of Accounting Series Release No. 165 - Smith, David B. (Journal of Accounting Research, 1988)
Auditing, Auditor change, Auditor change disclosure, Delayed hiring